Greece : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper analyzes insolvency and enforcement issues in Greece. The Greek insolvency and creditor rights framework has improved since the onset of the crisis as a result of successive reforms. Nonetheless, it remains underutilized, fragmented, and distortive, and is not supported by an adequate institutional setting. This is because many of the reforms undertaken in recent years were not part of a coordinated and comprehensive nonperforming loan resolution strategy, but were instead piecemeal and taken without proper stakeholder consultation and impact analysis. Also, the frequent and uncoordinated reforms have undermined legal predictability and certainty. This situation of distress, if left unaddressed, affects enterprises, households and financial and public creditors by preventing investment, credit, and consumption from recovering.